2013
DOI: 10.5539/ijms.v5n6p73
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Regret Concerning the Process of Purchasing and the Regret Concerning after the Purcashing in the Context of Characteristic Properties

Abstract: The aim of this study is to investigate the relationship among general regret concerning the life, the regret concerning the process of purchasing and the regret concerning after the purchasing and to determine the characteristic properties which are effective on these three types of regret. This study is applied on the students of Eskisehir Osmangazi University and Karamanoglu Mehmetbey University and it is benefited from the convenience sampling in the study. The data of this study is collected via questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Given non-planning impulsivity reflects an inability to plan (Patton et al, 1995), these findings are in line with theoretical description by which regret due to a change in significance reflects regret caused by an individual's inability to predict the usefulness of a product in the future. Also, these findings are consistent with preview findings (Ekici & Dogan, 2013) showing that regret concerning after the process of purchasing which includes regret due to change insignificance, was associated with self-assessment planning ability.…”
Section: Discussionsupporting
confidence: 90%
“…Given non-planning impulsivity reflects an inability to plan (Patton et al, 1995), these findings are in line with theoretical description by which regret due to a change in significance reflects regret caused by an individual's inability to predict the usefulness of a product in the future. Also, these findings are consistent with preview findings (Ekici & Dogan, 2013) showing that regret concerning after the process of purchasing which includes regret due to change insignificance, was associated with self-assessment planning ability.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the regret with the alternative forgone increases. Ekici and Dogan (2013) also confirmed a positive relationship between the regret process of purchase and post-purchase levels. As per Ramprabha (2018), married women are more influenced by retail store factors than unmarried women.…”
Section: Introductionsupporting
confidence: 59%
“…But, since regret is a cognitive recognition, qualitative approaches like interviews can change the variable effects. According to the research done by Ekici and Dogan [19], it was confirmed that there's a positive relationship between regret concerning life and post-purchase levels. Post-purchase regret can significantly affect customer retention.…”
Section: Introductionmentioning
confidence: 93%